Characterization of mesenchymal stem cells derived from equine adipose tissue - Carvalho, A.m. [UNESP]; Yamada, A.l.m. [UNESP]; Golim, M.a. [UNESP]; Álvarez, L.e.c. [UNESP]; Jorge, L.l. [UNESP]; Conceição, M.l. [UNESP]; Deffune, Elenice [UNESP]; Hussni, C.a. [UNESP]; Alves, A.l.g. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2013)
Stem cell therapy has shown promising results in tendinitis and osteoarthritis in equine medicine. The purpose of this work was to characterize the adipose-derived mesenchymal stem cells (AdMSCs) in horses through (1) the assessment of the capacity of progenitor cells to perform adipogenic, osteogenic and chondrogenic differentiation; and (2) flow cytometry analysis using the stemness related markers: CD44, CD90, CD105 and MHC Class II. Five mixed-breed horses, aged 2-4 years-old were used to collect adipose tissue from the base of the tail. After isolation and culture of AdMSCs, immunophenotypic characterization was performed through flow cytometry. There was a high expression of CD44, CD90 and CD105, and no expression of MHC Class II markers. The tri-lineage differentiation was confirmed by specific staining: adipogenic (Oil Red O), osteogenic (Alizarin Red), and chondrogenic (Alcian Blue). The equine AdMSCs are a promising type of adult progenitor cell for tissue engineering in veterinary medicine.

O uso de células tronco tem demonstrado resultados promissores na terapia da tendinite e osteoartrite na medicina equina. O objetivo deste trabalho foi caracterizar as células tronco mesenquimais derivadas do tecido adiposo (AdCTMs) em cavalos através da (1) avaliação da capacidade das células progenitoras para realizar a diferenciação adipogênica, osteogênica e condrogênica; e (2) através da análise por citometria de fluxo, utilizando os marcadores stemness relacionados: CD44, CD90, CD105 e MHC de Classe II. Cinco cavalos sem raça definida, de 2 a 4 anos de idade foram utilizados para a coleta do tecido adiposo da base da cauda. Após o isolamento e cultivo das AdCTMs, a caracterização imunofenotípica foi realizada pela citometria de fluxo. Houve alta expressão dos marcadores CD44, CD90 e CD105, e não houve expressão do MHC Classe II. A diferenciação foi confirmada pela coloração específica: adipogênica (Oil Red O), osteogênico (Alizarin Red), e condrogênico (Alcian Blue). As AdCTMs são um tipo promissor de células progenitoras adulta para a engenharia tecidual na medicina veterinária.
Caracterização das células tronco mesenquimais derivadas do tecido adiposo equino
Keywords: caracterização imunofenotípica; diferenciação; equino; tecido adiposo; célula tronco mesenquimal; immunophenotypic characterization; differentiation; equine; adipose tissue; mesenchymal stem cell